Effects of Municipal Wastewater Irrigation on Yield and Fertilizer Requirement of Wheat (Triticum aestivum L.) in Bangladesh (The Agriculturists, 2016)
Due to increasing scarcity of fresh water, use of unconventional water source (e.g., wastewater) in irrigation has now become important. However, inclusive information on the effects of wastewater on crop production and soil health is necessary for such intervention. This study was designed to evaluate these effects by demonstrating the contribution of municipal wastewater (hereafter called wastewater) on yield and nutrient requirement of wheat (Triticum aestivum L.) cv Shatabdi. Five irrigation treatments - I1, I2, I3, I4 and I5  were tested in a Randomized Complete Block Design (RCBD) with three replications during November-March of 2007-2008, 2008-2009, 2009-2010 at the experimental field of the Bangladesh Agricultural University,  Mymensingh. The treatments I2-I5 consisted of blended wastewater and I1 of fresh water (control). The ratio of wastewater to total irrigation water was 0.25, 0.50, 0.75 and 1.0 in I2, I3, I4 and I5, respectively. Wheat was cultivated with three irrigations and recommended doses of fertilizer in three consecutive years. Wastewater contained nitrogen (N), phosphorus (P) and potassium (K) @ 17.5, 3.7 and 10.3 mg/L, respectively, and irrigation by raw wastewater (I5) contributed 19.1, 15.1 and 21.7% of the recommended N, P and K, respectively. Biomass yield increased with increasing fraction of wastewater in irrigation. Grain yield increased for the wastewater fraction of 0.50 - 0.75 in irrigation but decreased when irrigation was applied by raw wastewater. Excess fertilizer (under I5) boosted up growth of wheat, but did not contribute to the grain yield. Number of grains per spike; and grain, straw and biological yields significantly (p = 0.05) increased due to the contribution of wastewater. Wastewater significantly improved grain and biomass production, with the largest value obtained in I4 (4.61 t/ha grain yield and 11.36 t/ha biomass yield).  Raw wastewater in combination with recommended fertilizer doses caused over-fertilization that contributed only in biomass production but not in grain production of wheat and irrigation by wastewater substantially reduced fertilizer requirement of wheat.The Agriculturists 2016; 14(1) 01-14